2007
DOI: 10.1007/s00464-007-9576-2
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y gastric bypass as a re-do procedure for failed restricive gastric surgery

Abstract: Based on the literature, we can presume that restrictive surgery for morbidly obese patients will require many reoperations in the future. The standard operation of choice is RYGBP. In our study this procedure showed a higher, but not significantly early morbidity rate when the indication for re-do surgery was a technical complication of the initial procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(20 reference statements)
2
22
1
Order By: Relevance
“…There was one (2.6%) conversion in the laparoscopy group, a 14.2% (6/42) complication rate, a 9.5% (4/42) reoperation rate, no mortality, and a mean hospital stay of 3.36 days. Van Dessel et al [22] reported 36 conversions after VBG, AGB, or GS with a 27.8% (10/36) conversion rate (10/36). There were 11 patients with early complications, 2 of which needed reoperation and 6 with late complications (overall 17/36 or 47%).…”
Section: Discussionmentioning
confidence: 99%
“…There was one (2.6%) conversion in the laparoscopy group, a 14.2% (6/42) complication rate, a 9.5% (4/42) reoperation rate, no mortality, and a mean hospital stay of 3.36 days. Van Dessel et al [22] reported 36 conversions after VBG, AGB, or GS with a 27.8% (10/36) conversion rate (10/36). There were 11 patients with early complications, 2 of which needed reoperation and 6 with late complications (overall 17/36 or 47%).…”
Section: Discussionmentioning
confidence: 99%
“…In experienced hands, revisional bariatric surgery can be performed laparoscopically in a safe way with low complication ratesand excellent results on additional weight loss. [29,30] If metabolic surgeons want to gather and keep support in the provider community, they have the responsibility to report the results of primary and secondary bariatric procedures, hospitalization, complication rates and healthcare costsin a standardized way. There is need to reduce invasiveness of bariatric therapy and re-interventions in the futureto enhance societal support, and more importantly, to enable the treatment of more individuals.…”
Section: Resultsmentioning
confidence: 99%
“…We certainly realize that the number of patients we are reporting after revisional bariatric surgery seems to be low and conclusions on mortality and morbidity rates are limited. However, so far most of the available literature on conversions from banding to gastric bypass deals with lower numbers (Table 3) [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%